Sosialisasi Urgensi ilmu (Kuliah) Bagi Generasi Muda di Pondok Salaf Nurul Hidayah Lewisadeng Bogor - Ali, Agus; Taufik, Raden Dimas; Salsabil, Nabila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Science is very important for every individual and can even increase human dignity. In Islam, seeking knowledge is also a worship to Allah and there are certain goals in the process of studying. The importance of having knowledge is to prove the power of Allah SWT. This goal is to strengthen human trust and faith in Allah SWT. With knowledge, humans can read the Qur'an which contains all the problems that exist on this earth. Science also allows humans to examine the universe created by God.This type of research is field research, namely research conducted by being directly at the object, especially in an effort to collect data and various information. While the nature of this research is qualitative, namely the form of research as a research procedure as a research procedure that produces descriptive data in the form of written or oral words from the people or actors observed.PKM regarding the socialization of the Urgency of Knowledge (Lectures) for the Young Generation and is also sustainable is aimed at teachers at the Islamic boarding school students of Pondok Salaf Nurul Hidayah, Bogor Regency, which has been carried out well. This PKM regarding the socialization of the Urgency of Knowledge (Lecture) for the Young Generation and is also sustainable is aimed at the students of Pondok Salaf Nurul Hidayah, Bogor Regency, getting an enthusiastic response from the participants. Two questions were obtained from socialization participants (santri-students) regarding the material Urgency of knowledge at the pesantren. They hoped that there would be socialization/seminar/workshop activities again related to the Urgency of knowledge (Lectures) for the Young Generation which is good and correct, directed, and also sustainable. Keywords: Socializatio, the Urgency of Knowledge (Lecture), for Young Generation